Jawabanmu

2014-09-13T06:22:44+07:00
A. 4 (x + 5)² = 4 (x + 5) (x + 5)
                 = 4 (x² + 5x + 5x + 25)
                 = 4 (x² + 10x +25)
                 = 4x² + 40x + 100
b. 3 (2p - 4)² = 3 (2p - 4) (2p - 4)
                   = 3 (4p² - 8p - 8p  + 16)
                   = 3 (4p² - 16p + 16)
                   = 12p² - 48p + 48
c. 5 (3p - 5q)² = 5 (3p -5q) (3p - 5q)
                     = 5 (9p² - 15pq - 15pq + 25q²)
                     = 5 (9p² - 30pq + 25q²)
                     = 45p² - 150pq + 125q²
1 5 1